2016
DOI: 10.1111/acer.13123
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of the Minimum Legal Drinking Age on Alcohol‐Related Chronic Disease Mortality

Abstract: Background The minimum legal drinking age (MLDA) of 21 has been associated with a number of benefits compared to lower MLDAs, including long-term effects, such as reduced risk for alcoholism in adulthood. However, no studies have examined whether MLDA during young adulthood is associated with mortality later in life. We examined whether individuals exposed to permissive MLDA (< 21) had higher risk of death from alcohol-related chronic disease compared to those exposed to the 21 MLDA. Because prior work suggest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
7
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 38 publications
2
7
0
1
Order By: Relevance
“…First, supporting previous research on increased alcohol availability, we found that lowering the legal age limit for alcohol purchases can have long‐term alcohol‐related health consequences 2, 5, 6, 7, 8, 9. Secondly, the study provides further evidence that alcohol consumption during adolescence is associated with later health problems 16, 17, 18.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…First, supporting previous research on increased alcohol availability, we found that lowering the legal age limit for alcohol purchases can have long‐term alcohol‐related health consequences 2, 5, 6, 7, 8, 9. Secondly, the study provides further evidence that alcohol consumption during adolescence is associated with later health problems 16, 17, 18.…”
Section: Discussionsupporting
confidence: 88%
“…Previous research, using a natural experiment setting of a policy change, has investigated the short‐ and long‐term effects of changing the legal age limit for alcohol purchases on alcohol consumption and alcohol‐related harm 5, 6, 7, 8, 9, 10. One area where research is scarce, but potential costs are high, concerns the association between increased alcohol availability during adolescence and the risk of disability pension.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the alcohol index used in the present study only captures a small proportion of the diseases and injuries attributable to alcohol 38. Plunk and colleagues found an association between a lowered legal drinking age and increased risk of death due to alcoholic liver disease, liver disease not specified as alcohol related, and cancer of the lip, oral and pharynx 7. The alcohol index was used to define the outcome as all diagnoses included require the individual to consume alcohol.…”
Section: Discussionmentioning
confidence: 79%
“…Так, A. Plunk и соавт. [23] в 2016 г. показали, что увеличение минимального возраста потребления алкогольной продукции, вероятно, защищает от риска возникновения хронического алкоголь-ассоциированного заболевания на протяжении всей жизни. Примечательно, что эту тенденцию авторы наблюдали у тех, кто не посещал колледж, что, на наш взгляд, делает результаты еще более убедительными, поскольку уровень образования нередко влияет на уровень потребления алкоголя.…”
unclassified